Perbandingan Pengaturan Restorative Justice dalam Sistem Peradilan Pidana Indonesia dan Selandia Baru - Ahmad Rasyifin; Akhmad Riduan; David Fendiantoro; Meilina Permata Hati; Salamah Salamah (PT. Banjarese Pacific Indonesia, 2026)
The development of the modern criminal justice system demonstrates a paradigm shift from a retributive approach toward a restorative approach that emphasizes victim recovery, offender accountability, and the restoration of social relationships affected by criminal acts. This study aims to analyze the regulation of restorative justice within the criminal justice systems of Indonesia and New Zealand and to examine the relevance of the Family Group Conference model in strengthening restorative justice policies in Indonesia. The study employs a descriptive-analytical normative legal method using statutory, conceptual, and comparative legal approaches. Research data were obtained through a literature review of primary legal materials consisting of legislation and legal policies governing restorative justice in Indonesia and New Zealand, as well as secondary legal materials in the form of books, national and international scientific journals, and relevant academic publications. The findings indicate that Indonesia has adopted restorative justice through various sectoral regulations, including Prosecutor Regulation Number 15 of 2020 and Police Regulation Number 8 of 2021; however, these regulations remain fragmented and have not been comprehensively integrated into the criminal justice system. In contrast, New Zealand has positioned restorative justice as an integral component of its criminal justice system through the Family Group Conference mechanism, which actively involves victims, offenders, families, and communities in the case resolution process. The novelty of this study lies in its comparative analysis of the legal frameworks governing restorative justice in both countries and its assessment of the Family Group Conference model as a reference for developing a more integrated restorative justice system in Indonesia. This study highlights the importance of regulatory harmonization, strengthening victim and community participation, and expanding comparative legal studies on restorative justice as references for future research and criminal justice reform oriented toward substantive justice.